Stellate Ganglion Block for the Treatment of Posttraumatic Stress Disorder: A Randomized, Double-Blind, Controlled Trial. Issue 4 (July 2016) - Hanling, Steven R.; Hickey, Anita; Lesnik, Ivan; Hackworth, Robert Jeremy; Stedje-Larsen, Eric; Drastal, Carol Anne; McLay, Robert N.
Abstract : Objective: In this study, we aimed to determine if stellate ganglion block (SGB) could reduce symptoms of posttraumatic stress disorder (PTSD) in comparison with sham therapy in military service members. Methods: In a randomized trial in which both participants and assessors were blind, participants with PTSD received either an SGB or a sham procedure. Posttraumatic stress disorder symptoms were measured using the CAPS (Clinician-Administered PTSD Scale) and self-report measures of PTSD, depression, anxiety, and pain. Subjects underwent assessment before the procedure and at 1 week, 1 month, and 3 months after the procedure. Patients receiving sham injections were allowed to cross over to the treatment group, and participants who maintained criteria for PTSD were allowed to receive a second SGB treatment. Results: Posttraumatic stress disorder, anxiety, and depression scores all showed improvement across time, but there was no statistically or clinically relevant difference in outcomes between the active and control groups. Individuals who crossed over from sham treatment to SGB similarly showed no greater improvement with the SGB treatment. Improvement in CAPS was greater with a second SGB treatment than after the first treatment. Conclusions: Although previous case series have suggested that SGB offers an effective intervention for PTSD, this study did not demonstrate any appreciable difference between SGB and sham treatment on psychological or pain outcomes. Future studies should examine if differences in treatment methods or patient population could allow individuals with PTSD to benefit from SGB, but current evidence does not support widespread or indiscriminant clinical use of the procedure for PTSD.